A BODIPY-based activatable nanotheranostics for tumor hypoxia imaging and hypoxia-induced drug resistance reversal. (December 2022) - Li, Xudong; Wang, Yuran; Chen, Hui; Zheng, Yilin; Chen, Haijun; Li, Xiumei; Gao, Yu
Highlights: An amphiphilic BODIPY dye-modified chitosan (CsB) with hypoxia-triggered fluorescence imaging ability was synthesized. CsBANs self-assembled by CsB and AZD9291 achieved hypoxia-responsive imaging and synergistic photothermal/targeted molecular therapy. CsBANs showed satisfactory anticancer effects in NSCLC cell lines and in xenograft mouse model to overcome hypoxia-induced drug resistance. CsBANs show great potential as a hypoxia-activated nanotheranostic platform to deal with hypoxia-related diseases. Abstract: Tumor hypoxic microenvironment contributes to AZD9291 (osimertinib) resistance in non-small cell lung cancer (NSCLC). Developing hypoxia-triggered theranostic formulation for simultaneous hypoxia tumor imaging and oxygen-independent photothermal therapy (PTT) will be an effective strategy to overcome AZD9291 resistance under hypoxic conditions. Herein, we designed and synthesized a boron-dipyrromethene (BODIPY) dye-modified chitosan (CsB) linked through a hypoxia-responsive azobenzene group and fabricated a nanoplatform CsBANs self-assembled by CsB and AZD9291 to achieve hypoxia-responsive imaging and synergistic PTT/targeted molecular therapy. CsBANs exhibited excellent cellular uptake efficiency and hypoxia imaging capacity either in two-dimensional NSCLC cell cultures under hypoxia or in multicellular tumor spheroids. The in vitro and in vivo results showed that the photothermal effects of BODIPY and AZD9291 could induce satisfactory anticancer effects in NSCLC cell lines and in xenograft mouse model. Hence, this work presents a promising hypoxia-activated nanotheranostic platform to deal with hypoxia-induced AZD9291 resistance and for other hypoxia-related diseases. Graphical abstract: Image, graphical abstract